Overconfidence Bias and Islamic Financial Literacy in Shaping Generation Z’s Sharia Stock Investment Decisions: Evidence from Indonesia’s Sharia Capital Market - Mhd Adjie Permana Hasibuan; Muhammad Ikhsan Harahap; Nuri Aslami (Jurnal Investasi Islam, 2026)
The intersection of cognitive bias and normative financial knowledge presents a theoretically significant tension in Islamic behavioral finance, particularly among digitally exposed young investors. This study investigates whether overconfidence bias and Islamic financial literacy operate as competing or complementary mechanisms in shaping sharia stock investment decisions among Generation Z investors in Indonesia. Using a Second-Order Confirmatory Factor Analysis (Second-Order CFA) approach within the SEM-PLS framework (Hair et al., 2021), data were collected from 200 active sharia stock investors aged 17–27 years in Medan City. All constructs demonstrated satisfactory measurement quality under the hierarchical component model. Findings reveal that both overconfidence bias (β = 0.582; t = 17.682; p = 0.000) and Islamic financial literacy (β = 0.586; t = 16.478; p = 0.000) positively and significantly influence investment decisions, collectively explaining 81.1% of the variance (R² = 0.811). Critically, the positive effect of overconfidence reflects heightened decision activity and trading aggression—not improved decision quality—as overconfident investors assume elevated risk exposure inconsistent with the prudence demanded by Islamic muamalah principles. The near-equivalent path coefficients reveal a behavioral paradox: irrational psychological impulse and rational Islamic knowledge exert comparable but theoretically opposed influences on investment behavior—a tension underexplored in the sharia investment literature. These findings challenge the assumption that Islamic financial literacy alone can suppress cognitive irrationality, and call for integrated behavioral finance education addressing both cognitive and metacognitive dimensions of investment decision-making among young Muslim investors in Indonesia’s sharia capital market.